2019
DOI: 10.1111/nph.15804
|View full text |Cite
|
Sign up to set email alerts
|

Inherited allelic variants and novel karyotype changes influence fertility and genome stability in Brassica allohexaploids

Abstract: Summary Synthetic allohexaploid Brassica hybrids (2n = AABBCC) do not exist naturally, but can be synthesized by crosses between diploid and/or allotetraploid Brassica species. Using these hybrids, we aimed to identify how novel allohexaploids restore fertility and normal meiosis after formation. Chromosome inheritance, genome structure, fertility and meiotic behaviour were assessed in three segregating allohexaploid populations derived from the cross (B. napus × B. carinata) × B. juncea using a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 69 publications
5
57
0
Order By: Relevance
“…Additionally, in wheat, MSH7 has been identified as a candidate Ph2 gene (Dong et al, 2002;Lloyd et al, 2007). In B. napus, one of the candidate meiotic instability loci identified by Gaebelein et al (2019) was MSH2 on chromosome C3. Gonzalo et al (2019) demonstrated that when MSH4 was reduced to only one functional copy HeR was decreased in B. napus allohaploids, but homologous recombination in allotetraploids was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in wheat, MSH7 has been identified as a candidate Ph2 gene (Dong et al, 2002;Lloyd et al, 2007). In B. napus, one of the candidate meiotic instability loci identified by Gaebelein et al (2019) was MSH2 on chromosome C3. Gonzalo et al (2019) demonstrated that when MSH4 was reduced to only one functional copy HeR was decreased in B. napus allohaploids, but homologous recombination in allotetraploids was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HE patterns across subgenomes were found to be a largely random between individuals. However, individuals with more BnA to BnC exchange events (where BnC regions replaced BnA segments) had lower pollen counts, potentially related to the meiotic instability they have been shown to introduce (24). This decline pollen viability may explain why natural and resynthesized B. napus lines grown in the field show more exchange events where BnA regions replace BnC regions (46) .…”
Section: Discussionmentioning
confidence: 99%
“…Given that gene expression level dominance occurs instantly following the initial hybridization event (15) , resynthesized allopolyploids are the ideal system to investigate the establishment and escalation of subgenome dominance. Few studies have used multiple independently derived resynthesized allopolyploids to investigate the variability of subgenome dominance (21)(22)(23)(24)(25)(26) . Thus it remains unclear the extent to which the emergence of subgenome dominance is a result of pre-existing characteristics of the diploid progenitors or due to independent and non-recurrent events during polyploid formation.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent recent example of this process is provided by genomic investigations of allotetraploid peanut, in which regions of both A and B subgenomes had been replaced by copies of the other subgenome (AABB -> AAAA or BBBB) (Bertioli et al, 2019), putatively as a result of fixation of these homoeologous exchanges after a single allopolyploidization event. On the other hand, a possible outcome of biased replacement of one subgenome with the other subgenome, as has been documented to occur via fertility-based selection in some species (e.g., Gaebelein et al, 2019), could make an even more interesting pattern: an "autopolyploid" may result, but possibly one that appears to have small genomic regions introgressed from another species (Figure 2). Recently, synthetic rice polyploids formed by hybridization between japonica and indica subspecies also revealed directional loss of one subgenome through selection for the products of HEs (Zhang et al, 2019).…”
Section: Homoeologous Exchanges and Segmental Allopolyploidymentioning
confidence: 99%